THE EFFECT OF CONSUMER AFFINITY, COUNTRY OF ORIGIN AND PERCEIVED RISK ON PURCHASE DECISIONS - Raysya Nusantara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2022)
The purpose of this research is to see the extent of the influence of Consumer Affinity, The Effect of Country of Origin and Perceived Risk on consumers in making purchasing decisions for products originating from affinity countries. The type of research used is quantitative research with a method or approach through survey research. This study collected 150 respondents by distributing questionnaires in the form of Google Form. The sampling method used purposive sampling to ensure that the researcher got the right sample, in this study conducted on generation Z in Pontianak who had been exposed to South Korean culture virtually. The data analysis tool used is Multiple Linear Regression using SPSS version 25. The findings of this study indicate that in Pontianak, Consumer Affinity, Country of Origin Effects and Perceived Risk have a significant effect on purchasing decisions of South Korean affinity country products.